Silica Nanoparticle Acute Toxicity on Male Rattus norvegicus Domestica: Ethological Behavior, Hematological Disorders, Biochemical Analyses, Hepato-Renal Function, and Antioxidant-Immune Response - Almanaa, Taghreed N.; Aref, Mohamed; Kakakhel, Mian Adnan; Elshopakey, Gehad E.; Mahboub, Heba H.; Abdelazim, Aaser Mohamed; Kamel, Samar; Belali, Tareg M.; Abomughaid, Mosleh M.; Alhujaily, Muhanad; Fahmy, Esraa M.; Ezzat Assayed, Mohamed; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
ABSTRACT With the extensive production and various applications of silica nanoparticles (SiNPs), there is a controversy regarding the ecotoxicological impacts of SiNPs. Therefore, the current study was aimed to assess the acute toxicity of silica nanoparticles in male Rattus norvegicus domestica after 24 and 96 h. Hematological, serum biochemical, stress biomarkers, and immune-antioxidant parameters were addressed. The chemical composition, crystal structure, and the particle shape and morphology of SiNPs were investigated using XRD, FTIR, BET, UV-vis, and SEM, while TEM was used to estimate the average size distribution of particles. For the exposure experiment, 48 male rats were divided into four groups (12 rat/group) and gavaged daily with different levels of zero (control), 5, 10, and 20 mg of SiNPs corresponding to zero, 31.25, 62.5, 125 mg per kg of body weight. Sampling was carried out after 24 and 96 h. Relative to the control group, the exposure to SiNPs induced clear behavioral changes such as inactivity, lethargy, aggressiveness, and screaming. In a dose-dependent manner, the behavior scores recorded the highest values. Pairwise comparisons with the control demonstrated a significant (p<0.05) decrease in hematological and immunological biomarkers (lysozymes and Alternative complement activity, ACH50)) with a concomitant reduction in the antioxidant enzymes (Catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD)) in all exposed groups to SiNPs. On the contrary, there was a noticeable increase in biochemical parameters (glucose, cortisol, creatinine, urea, low-density lipoproteins (LDL), high-density lipoproteins (HDL), total protein, and albumin) and in the hepato-renal indicators including alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) of all SiNPs-exposed groups. It was observed that the SiNPs induced acute toxicity, either after 24h or 96h, post-exposure of rat to SiNPs evidenced by ethological changes, hepato-renal dysfunction, hyperlipemia, and severe suppression in the hematological, protein, stress, and immune-antioxidant biomarkers reflecting impaired physiological status. The obtained outcomes create the foundation for future research to consider the acute toxicity of nanoparticles to preserve human health and sustain the environment.